Commerce: Help bigger palm oil yields to save land - Pinto, A. de; Wiebe, Keith D.; Pacheco, P. (Springer, 2017)
Technological innovation in oil-palm farming could help both to boost yields of palm oil and to reduce deforestation, but only if higher productivity causes palm-oil prices to drop sufficiently to discourage additional cultivation. If prices stay high, the demand for land is likely to go up in the push for ever-larger profits.